Analisis Penerimaan Mahasiswa Indonesia Terhadap Teknologi Digital Layanan Distribusi Konten Audio Melalui Podcast - Erlangga Norman Wicaksana; Asif Faroqi; Anita Wulansari (STMIK Banjarbaru, 2022)
Spotify is one of the most popular platforms used to listen to podcasts in Indonesia, especially for students. To be able to continue to provide support for the survival of the audio streaming industry in an effort to improve services in a better direction, it is important to know the factors that support the acceptance of services from the Spotify podcast service. This study aims to analyze what factors influence users to use the Spotify podcast service. The analytical method used is the Technology Acceptance Model (TAM). Data were obtained from 438 Spotify podcast users, and analyzed using SmartPLS 3 software. The results showed that the factors influencing the use of the Spotify podcast application consisted of Perceived Usefulness, Perceived Ease of Use, Perceived Self-Efficacy, and Perceived Enjoyment. The Social Influence factor has no significant effect on usage interest.Keywords: Spotify; Technology Acceptance Model; SmartPLS 3 Abstrak. Spotify adalah salah satu platform paling populer yang digunakan untuk mendengarkan podcast di Indonesia, khususnya para mahasiswa. Untuk dapat terus memberikan dukungan keberlangsungan hidup industri streaming audio ini dalam upaya meningkatkan layanan ke arah yang lebih baik, penting untuk diketahui faktor-faktor yang mendukung penerimaan layanan dari layanan podcast spotify. Penelitian ini bertujuan untuk menganalisis faktor-faktor apa saja yang mempengaruhi pengguna menggunakan layanan podcast Spotify. Metode analisis yang digunakan adalah Technology Acceptance Model (TAM). Data diperoleh dari 438 pengguna podcast Spotify, dan dianalisis menggunakan software SmartPLS 3. Hasil penelitian diperoleh bahwa faktor yang mempengaruhi penggunaan aplikasi podcast Spotify terdiri dari Perceived Usefulness, Perceived Ease of Use, Perceived Self-Efficacy, dan Perceived Enjoyment. Adapun faktor Social Influence tidak berpengaruh signifikan terhadap minat penggunaan.Kata kunci: Spotify; Technology Acceptance Model; SmartPLS 3